Management of chronic osteomyelitis of the tibia with life-threatening complications under negative pressure wound therapy and isolation of Helcococcus kunzii - Stanger, Katrin M.; Albert, Frauke; Kneser, Ulrich; Bogdan, Christian; Horch, Raymund E. (International Wound Journal, 2015)
We report the case of an 86-year-old man with severe wound infection originating from a chronic crural ulcer of the lower limb, which under negative pressure wound therapy led to excessive tissue necrosis and perforation of the anterior tibial artery. A swab taken 10 and 7 days preoperatively was positive for Helcococcus kunzii. H. kunzii has been described as a potentially pathogenic organism. The questions whether the negative pressure wound therapy itself caused the bleeding or the negative pressure wound therapy, which generates an anaerobic atmosphere, has triggered the growth and invasion of the facultative anaerobic bacterium H. kunzii and owing to the infection the artery perforated or whether the bacteria has no influence at all remain currently unanswered. After surgical debridement the signs of infection were completely eliminated, and a free musculocutaneous flap led to rapid healing of the wound. Following which H. kunzii was no longer detectable.
EVALuna2:7649